Pengaruh Likuiditas, Leverage, Operating Capacity, dan Sales Growth Terhadap Financial Distress (Studi pada Perusahaan Property, Real Estate, dan Konstruksi Bangunan yang Terdaftar di Bursa Efek Indonesia) - Anak Agung Istri Ratih Setia Dewi; Gede Juliarsa (Journal Of Business, Finance, and Economics (JBFE), 2025)
Financial distress is a situation where a company experiences financial difficulties before experiencing bankruptcy. This research aims to obtain empirical evidence regarding the influence of liquidity, leverage, operating capacity and sales growth on financial distress. The population in this research is all property, real estate and building construction companies listed on the Indonesia Stock Exchange (BEI) in 2023. Sample selection was carried out using a purposive sampling method and the number of samples obtained was 53 observational data. The data analysis technique used in this research is multiple linear regression analysis. The results of this research show that liquidity has a negative effect on financial distress, leverage has a positive effect on financial distress, operating capacity and sales growth has no effect on financial distress. The implication of this research is that it can confirm Signaling Theory.